Effect of Aqueous Extract from The Root Cortex of Aralia elata on Intestinal alpha-Glucosidases and Postprandial Glycemic Response in Mice - Harumi Ohno; Junya Nagai; Tomonori Kurokawa; Masaru Sonoda; Ryoko Yumoto; Mikihisa Takano (International Journal of Phytomedicine, 2012)
The bark and root cortex of Aralia elata have been used as traditional medicine for the treatment of diabetes mellitus in Oriental countries including China, Korea and Japan. The purpose of this study was to assess the influence of aqueous extract from the root cortex of Aralia elata on the intestinal alpha-glucosidase activity and the glycemic response after ingestion of carbohydrates. In in vitro intestinal alpha-glucosidase assay, water extract from the root cortex of Aralia elata inhibited the activities of intestinal maltase and trehalase in a concentration-dependent manner with IC50 values of 0.45 mg/mL and 0.65 mg/mL, respectively. The fraction which was extracted with water from the root cortex of Aralia elata has a stronger inhibitory effect on the intestinal alpha-glucosidases than that extracted with pure ethanol. In in vivo postprandial glycemic response study using mice, the water extract from the root cortex of Aralia elata (0.125 g/kg) significantly inhibited the increase in plasma glucose concentration induced by oral administration of maltose and trehalose, but not glucose. The observation indicates that the reduced glucose response to disaccharides in mice with the water extract was, at least in part, due to the inhibition of intestinal alpha-glucosidase activity. These findings might support the usefulness of a water-based preparation of the root cortex of Aralia elata, which has been long used in traditional medicine to treat diabetes mellitus.